A Review of Ureaplasma diversum: A Representative of the Mollicute Class Associated With Reproductive and Respiratory Disorders in Cattle - Santos Junior, Manoel Neres; Macêdo Neres, Nayara Silva de; Campos, Guilherme Barreto; Bastos, Bruno Lopes; Timenetsky, Jorge; Marques, Lucas Miranda (Frontiers in Veterinary Science, 2021)
The Mollicutes class encompasses nonwalled microbes with a reduced genome. They may infect plants, insects, humans, and animals including those on farms and in livestock. Ureaplasma diversum is a mollicute related to decreased reproduction mainly in the conception rate in cattle, as well as weight loss and decreased quality in milk production. Therefore, U. diversum infection contributes to important economic losses, mainly in large cattle producing countries such as the United States, China, Brazil, and India. The characteristics of mollicutes, virulence, and pathogenic variations make it difficult to control their infections. Genomic analysis, prevalence studies, and immunomodulation assays help better understand the pathogenesis of bovine ureaplasma. Here we present the main features of transmission, virulence, immune response, and pathogenesis of U. diversum in bovines.